KOMITMEN ORGANISASI GURU MEMEDIASI KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI KOLEKTIF GURU TERHADAP KINERJA GURU SMK SWASTA SE-KOTA SEMARANG (Students' Journal of Economic and Management, 2013)
The aims of this research is to examine and analyze of transformational leadership, teacher collective efficacy and teachers organizational commitment on teacher performance. And examine and analyze of teachers organizational commitment to be mediation variable between transformational leadership and teacher collective efficacy on teacher performance. Population in this research is the teacher of SMK Swasta Se-Kota Semarang with a total data sample of 340 respondents are taken randomly from 72 SMK in Semarang City. To test the hypothesis proposed in this model used 59 indicators variables studied. The results of data analysis shows there is positive effect and significant between transformational leadership and teacher collective efficacy on teachers organizational commitment. There is positive effect and significant between transformational leadership and teachers organizational commitment on teacher performance. There are positive effect and no significant between teacher collective efficacy on teacher performance. The test results indicate mediation of variable teachers organizational commitment have been mediated the transformational leadership and teacher collective efficacy on teacher performance. Keywords : Transformational Leadership, Teacher Collective Efficacy, Teacher Organizational Commitment and Teacher Performance.